The effects of spirituality on social entrepreneurship from Islamic perspective - Mhd. Sarif, Suhaimi; Ismail, Yusof; Paiman, Luqmanulhakim (2013)
Spirituality in social entrepreneurship has formed a considerable awareness among the Muslim scholars in recent times. Although much scholarly work exists regarding spirituality, however, most were carried out from the western perspective. A previous Social entrepreneurship literature has been based on behavior, intentions, and contextual variables and ignores or subordinates spiritual concepts. As social entrepreneurship includes innovative programs to improve livelihood to those who have no financial power, thus, it is the duty of the Muslim entrepreneurs to take initiative and innovate social security to satisfy the needs of the society. Realizing the current situation regarding spirituality in Islam and its effects on entrepreneurial outcomes, this exploratory study aims to explore how spirituality effects on social entrepreneurship from Islamic perspective which continues to create meaning for the Muslim entrepreneurs. Based on the feedback of 20 women social entrepreneurs in Klang Valley, there are six reasons for them to venture into social entrepreneurship. These reasons are paired with the key Islamic spirituality for social entrepreneurship that is in line with the objective (maqasid) of the religion on the social responsibility. The results from the qualitative research method are not generalizable, but they could give some insights to Muslim scholars, policy makers and lawmakers to focus more the social entrepreneurship. The future study should use triangulation method and to involve all stakeholders to produce more rigorous and comprehensive results and contribution to the theory and practice.